2010
DOI: 10.1002/cncr.25621
|View full text |Cite
|
Sign up to set email alerts
|

A prognostic model for soft tissue sarcoma of the extremities and trunk wall based on size, vascular invasion, necrosis, and growth pattern

Abstract: BACKGROUND:In soft tissue sarcoma, better distinction of high-risk and low-risk patients is needed to individualize treatment and improve survival. Prognostic systems used in clinical practice identify high-risk patients based on various factors, including age, tumor size and depth, histological type, necrosis, and grade. METHODS: Whole-tumor sections from 239 soft tissue sarcomas of the extremities were reviewed for the following prognostic factors: size, vascular invasion, necrosis, and growth pattern. A new… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
25
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(34 citation statements)
references
References 37 publications
8
25
0
1
Order By: Relevance
“…We have recently identified infiltrative tumour growth pattern as a predictor of local and distant tumour recurrences in STS 28 39 40. The present work provides yet another validation of the prognostic importance of growth pattern, but also identifies a correlation between infiltrative growth pattern and ezrin expression (OR=3.1, p=0.03).…”
Section: Discussionsupporting
confidence: 69%
“…We have recently identified infiltrative tumour growth pattern as a predictor of local and distant tumour recurrences in STS 28 39 40. The present work provides yet another validation of the prognostic importance of growth pattern, but also identifies a correlation between infiltrative growth pattern and ezrin expression (OR=3.1, p=0.03).…”
Section: Discussionsupporting
confidence: 69%
“…This was confirmed in subsequent studies and led to the inclusion of necrosis in a four point prognostic model for sarcoma [58,59].…”
Section: Tumor Necrosis In Other Solid Organ Malignanciesmentioning
confidence: 72%
“…Numerous studies have identified clinical prognostic factors that could influence survival and local recurrence of soft tissue sarcoma (Behranwala et al 2004; Carneiro et al 2011; Coindre et al 1996; Collin et al 1987; Eilber et al 2004; Eilber et al 2003; Gaynor et al 1992; Heise et al 1986; Kattan et al 2002; Lahat et al 2008; McKee et al 2004; Mutter et al 2012; Pisters et al 1996; Ramanathan et al 1999; Riad et al 2004; Rööser et al 1988; Singer et al 1994; Stefanovski et al 2002; Stojadinovic et al 2002; Stotter et al 1990; Trojani et al 1984; Ueda et al 1988; Zagars et al 2003). Soft tissue sarcomas are characterized by aggressive histological invasiveness, which has been correlated with their prognosis (Gustafson et al 2003; Carneiro et al 2011). Almost all high grade sarcomas show histological extracapsular invasion.…”
Section: Discussionmentioning
confidence: 99%